Effective Analytic and Remotely Monitoring Smart Drug Delivery System based on IoMT with KNN classifier of Epilepsy Patients - et. al., Mr.Pradeep raj M S, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Chronic, non-communicable brain disorder, epilepsy is one of the most severe neurologic disorders. Worldwide, about 50 million individuals (2.5 percent) have Epilepsy, rendering it one of the world's most severe neurological disorders. [1]. About 80% of individuals with epilepsy work in countries with small to modest income. A medically refractory solution for the seizure control for a large fraction of affected patients. Here we explain the IMoT structure for a single drug delivery network. This has resulted in injection of drugs when seizure seizures have been identified. A powerful micro-pump electromagnetically powered with a polydimethylsiloxane (PDMS) diaphragm was used to distribute the drug. Simulink ® and ThingspeakTM were the prototype for the solution. The findings of the simulation reveal that the device proposed preserves high precision performance while substantially reducing power usage (8-26 %)..